If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c = b + bcd Solving c = b + bcd Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1bcd' to each side of the equation. -1bcd + c = b + bcd + -1bcd Combine like terms: bcd + -1bcd = 0 -1bcd + c = b + 0 -1bcd + c = b Reorder the terms: -1b + -1bcd + c = b + -1b Combine like terms: b + -1b = 0 -1b + -1bcd + c = 0 The solution to this equation could not be determined.
| x^2-8x+16=2x+16 | | 6w^2+31w+40=0 | | 5(x-4)=4-3x | | x+2+3+3+3-3=51 | | 2ln(x+9)-8lnx= | | lne^3x= | | 9(2y-9)-(8y+5)= | | 13+18x=535 | | 12+20x=132 | | (5x+1)(4x^2+2x+3)= | | 3t=-2 | | 7x^4-63x^2=0 | | 8b-6a-5a+6b= | | 3x^3=12 | | 4r=4 | | 18x^2=6x^4 | | 9p+7p+6p= | | 2x+15x= | | 59-7x=20x+17 | | x=14-8 | | 6(r-3)-2(r+5)+10= | | 56-3x=10x+17 | | p-7=9 | | 92-2x=43x+17 | | 2x^3+x^2+13x+84=0 | | 2x-4=10x-64 | | 112r^3+34r^2-6r=0 | | -4x-7y=5 | | 4(2u-3)=44 | | 2*6+{7*8}-67= | | 6a^2+13a=5 | | 18a^3b-39a^2b-15ab=0 |